CAR-γδ T cells: a new paradigm of programmable innate immune sentinels and their systemic applications in cancer and beyond - Fang, Xiang; Yan, Shixuan; He, Long; Deng, Changwen (Frontiers in Immunology, 2025)
This review systematically introduces the concept of CAR-γδ T cells as programmable innate immune sentinels, innovatively proposing to overcome multiple limitations of conventional CAR-αβ T cells in both solid tumor therapy and non-malignant disease contexts. The core innovation lies in the deep integration of γδ T cells’ natural immune features - including MHC-independent, anti-exhaustion phenotypic plasticity, and tissue-homing capability - with CAR engineering, potentially yielding synergistic effects between precise targeting, innate immune activation, and microenvironment modulation. We highlight recent advances in cutting-edge technologies such as multi-signal integration, genome editing, and the development of off-the-shelf CAR-γδ T cell platforms. Unlike previous reviews that focus narrowly on a single disease or signaling pathway, this work not only summarizes the biological characteristics of γδ T cells but also proposes a “δT-centric” engineering design principle and constructs a multi-disease application framework. In solid tumors, this approach may enable the remodeling of the immunosuppressive microenvironment and addresses tumor heterogeneity, whereas in non-malignant diseases-including fibrosis, autoimmune disorders, and chronic infections-it supports tissue homeostasis restoration. We propose that this paradigm could shift the perception of CAR-γδ T cells from conventional effector tools to dynamic immune hubs capable of responding adaptively to disease microenvironments. It proposes a novel conceptual and technological framework for both basic research and clinical translation across a broad spectrum of diseases.